Assessing the association between psoriasis and cardiovascular ischemia: An investigation of vascular endothelial growth factor, cutaneous angiogenesis, and arterial stiffness - Alpana Mohta; Achala Mohta; Bhikam C Ghiya (Wolters Kluwer Medknow Publications, 2023)
Background: Vascular endothelial growth factor (VEGF)-mediated angiogenesis's role in developing psoriasis and cardiovascular events has been established. However, the interplay between the two diseases regarding this cytokine remains an understudied area. Aim and Objectives: This case-control study aimed to investigate the relationship between VEGF-mediated angiogenesis and cardiovascular ischemia in patients with psoriasis. Materials and Methods: The study included 200 clinically diagnosed treatment-naïve cases of psoriasis and 200 controls. The VEGF level, cutaneous vascularity, and cardiovascular ischemia were measured between cases and controls. Cutaneous vascularity was assessed using non-invasive imaging technique such as laser doppler imaging (LDI) and measuring skin blood flow measurement (SBFM). Cardiovascular ischemia was evaluated using noninvasive techniques by measuring carotid intima-media thickness (CIMT) and pulse-wave velocity (PWV). The arterial vasa vasorum was evaluated using ultrasound imaging. Results: The study found a significant correlation between psoriasis severity and levels of VEGF (P < 0.001). Cases had significantly higher CIMT and PWV levels (P = 0.001 and <0.001, respectively). There was a significant positive correlation between the severity of psoriasis and the levels of cutaneous angiogenesis (r = 0.7, P < 0.001). Conclusion: According to this study, patients with psoriasis are at a higher risk of developing cardiovascular ischemia due to excessive angiogenesis associated with the condition. VEGF plays a key role in atheroma formation in psoriasis patients.